The impact of strategic leadership on improving employee performance at King Fahd Central Hospital in Jazan: An applied study on employees at King Fahd Central Hospital in Jazan - Mohajer, Jebreel Abdu (Journal of Economic, Administrative and Legal Sciences, 2025)
The problem: The problem of the study is summarized in the main question "What is the impact of strategic leadership on improving employee performance at King Fahd Central Hospital in Jazan?" Objective: The current study aims to know the impact of strategic leadership on improving employee performance at King Fahd Central Hospital in Jazan. Method and tools: The study used the descriptive analytical approach. The current study community consists of all employees at King Fahd Central Hospital in Jazan, numbering (108) individuals, and a sample. The sample members were selected using a simple random sample method. The study was applied to (40) employees of different ages, educational qualifications, and job positions. The distribution was done via a questionnaire and the data was analyzed using the statistical program (Spss). Results: The hospital’s senior management listens to the ideas, opinions, and suggestions of its employees. The hospital management works to follow up on the performance of employees on a regular basis and continuously evaluates. There is great interest from the hospital management in following up on the needs of employees and meeting them. The hospital management formulates clear and achievable goals at the lowest cost, which achieves progress within them. The sample members were collected by the hospital management. The hospital management continuously reviews the timetables and final timing of the tasks implemented. The senior management seeks to establish good and long-term relationships with the community it serves. The senior management seeks to have a long-term functional and administrative presence and promote good management from within its members. Recommendations: Develop a clear vision: Senior management should develop a clear strategic vision for the hospital, expressing future goals and ambitions. Promote effective communication: Create open communication channels between management and employees to ensure the exchange of information, ideas and feedback.